New Cellular Dimensions on Glioblastoma Progression - Portela, Marta (Neurosci Insights, 2020)
Gliomas are brain tumors originated from glial cells. The most frequent form of glioma is the glioblastoma (GB). This lethal tumor is frequently originated from genetic alterations in epidermal growth factor receptor (EGFR) and PI3K pathways. Recent results suggest that signaling pathways, other than primary founder mutations, play a central role in GB progression. Some of these signals are depleted by GB cells from healthy neurons via specialized filopodia known as tumor microtubes (TMs). Here, we discuss the contribution of TMs to vampirize wingless/WNT ligand from neurons. In consequence, wingless/WNT pathway is upregulated in GB to promote tumor progression, and the reduction of these signals in neurons causes the reduction of synapse number and neurodegeneration. These processes contribute to neurological defects and premature death.